Analysis of Students' Spatial Mathematical Ability viewed From The Florence Littauer Personality Type - Rismi, Dede; Rahayu, Diar Veni; Supratman, Supratman (PRISMA, 2025)
This research aims to analyze the spatial abilities of students in light of Florence Littauer's personality types and understanding of how students personality traits can influence their mathematical spatial abilities. This research is a qualitative research with an exploratory method. Data were collected from eighth-grade students of SMP Negeri 13 Tasikmalaya, . The subjects of the research are eight eighth-grade students from SMP Negeri 13 Tasikmalaya from each representing each of the four personality types. The research instruments included a personality type questionnaire, spatial ability tests, and unstructured interviews. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate variations in spatial ability achievement according to personality type. Students with a melancholic type demonstrated comprehensive mastery of all spatial indicators, while sanguine and phlegmatic students showed strengths in spatial perception as well as some aspects of visualization and rotation, though they still needed reinforcement in using geometric terminology and image representation. Meanwhile, choleric students exhibited strong mental rotation skills but experienced difficulties in visualizing objects from multiple perspectives and assembling shapes after manipulation. These findings contribute to mathematics education theory by highlighting the role of personality types in developing students’ spatial thinking skills